Combined spinal‐epidural anesthesia with hypobaric ropivacaine in sitting position significantly increases the incidence of hypotension in parturients undergoing cesarean section. Issue 4 (27th December 2016) - Xu, Zhendong; Shen, Fuyi; Zhang, Yueqi; Tao, Yiyi; Chen, Xiubing; Liu, Zhiqiang
Abstract: Aim: Maternal position during induction of combined spinal‐epidural anesthesia (CSEA) may affect hemodynamics and block characteristics. This study aimed to assess whether the sitting position is more likely to induce hypotension and higher block level than the lateral position in CSEA with hypobaric ropivacaine. Methods: Ninety American Society of Anesthesiologists physical status I and II parturients undergoing elective cesarean section were randomized into three groups: the sitting, left‐lateral, and right‐lateral position groups. The L3–4 interspace was selected as the puncture site, and subarachnoid injection of 2.5 mL 0.5% hypobaric ropivacaine was administered. After the epidural catheter was inserted and fixed, the patient's position was changed to the left‐leaning supine position. The blood pressure was measured once every 1 min followed by once every 3 min after the delivery. The sensory block level was regularly measured. Results: A total of 88 parturients were included in this study. The incidences of hypotension in the sitting, left‐lateral, and right‐lateral position groups were 72%, 38%, and 40%, respectively, P = 0.012. Incidence and total dose of the phenylephrine supplement in the sitting position group were significantly higher than in the other two groups. The sitting position group showed a significantly higher block level (T4 [T3, T4]) as compared to the left‐lateral (T6 [T5, T6]) and right‐lateral position groups (T6 [T4, T6]), P < 0.01. The Apgar scores of neonates at 1 min and 5 min, and the pH values of the umbilical arterial and venous blood were similar among the three groups. Conclusion: As compared to the lateral positions, CSEA with hypobaric ropivacaine in the sitting position is more likely to cause hypotension and excessively high block level.